Prevalence of ventilator associated pneumonia in Intensive Care Unit Hospital University Sains Malaysia - Teng Teik, Lim (2011)
Introduction : VAP is a common complication of patient who are receiving mechanical ventilation. This study aims to provide background prevalence, consequences and risk factors of VAP in HUSM. Methodology This was an observational study conducted in ICU HUSM. Patients were reviewed for background and interventional risk factors, length of stay and outcome. The study was conducted from January until December 2009. Result : A total of 194 patient fulfilled inclusion criteria and was followed up until discharge from ICU. Mean age of ICU patient was 47.53 years and mean duration of stay was 10.94 days. It was found that the VAP rate per 1000 ventilator days were higher than global VAP rates (19.57 days). DM poses additional risk for developing VAP with OR 2.182. Additionally intervention risk factor, transfering out of ICU (OR 1.402) and continuous sedation (OR 2.978) were statistically significant (p<0.05) for VAP development. Acinobacter sp. was found to be dominant pathogen from BAL of VAP patient. Conclusion : VAP rates in HUSM was found to be significantly higher than global rates. VAP lead to increase length of stay and is associated with DM, transfer out of ICU and continuous sedation. The main pathogen involved in HUSM VAP was Acinobacter sp.